2017
DOI: 10.1111/hae.13242
|View full text |Cite
|
Sign up to set email alerts
|

Episodic replacement of clotting factor concentrates does not prevent bleeding or musculoskeletal damage – the MUSFIH study

Abstract: Episodic CFC replacement over a large range of doses does not alter the natural course of bleeding in haemophilia or the musculoskeletal deterioration and should not be recommended as a long term option for treatment. Prophylaxis is the only way to preserve musculoskeletal function in haemophilia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 18 publications
0
21
0
1
Order By: Relevance
“…This has been clearly demonstrated in a recent long‐term joint outcome study conducted in several developing countries . Prophylaxis has demonstrated significant clinical advantages over episodic (on‐demand) treatment and is therefore recommended as the only way for long‐term CFC replacement therapy in haemophilia. In haemophilia A, both intermediate‐ (~15 IU/kg three times weekly) and higher‐dose (~30 IU/kg three times weekly) prophylaxis regimens have resulted in PWH achieving high physical activity levels and low bleeding frequencies, with both regimens achieving comparable quality of life outcomes .…”
Section: Principle 4 Regular Replacement Therapy With Clotting Factomentioning
confidence: 87%
See 2 more Smart Citations
“…This has been clearly demonstrated in a recent long‐term joint outcome study conducted in several developing countries . Prophylaxis has demonstrated significant clinical advantages over episodic (on‐demand) treatment and is therefore recommended as the only way for long‐term CFC replacement therapy in haemophilia. In haemophilia A, both intermediate‐ (~15 IU/kg three times weekly) and higher‐dose (~30 IU/kg three times weekly) prophylaxis regimens have resulted in PWH achieving high physical activity levels and low bleeding frequencies, with both regimens achieving comparable quality of life outcomes .…”
Section: Principle 4 Regular Replacement Therapy With Clotting Factomentioning
confidence: 87%
“…Prophylaxis has demonstrated significant clinical advantages over episodic (on‐demand) treatment and is therefore recommended as the only way for long‐term CFC replacement therapy in haemophilia. In haemophilia A, both intermediate‐ (~15 IU/kg three times weekly) and higher‐dose (~30 IU/kg three times weekly) prophylaxis regimens have resulted in PWH achieving high physical activity levels and low bleeding frequencies, with both regimens achieving comparable quality of life outcomes . Many developing and emerging economies have initiated prophylaxis at doses which are much lower than these contemporary doses in economically advanced countries, but not unlike what was used even in those countries several decades ago.…”
Section: Principle 4 Regular Replacement Therapy With Clotting Factomentioning
confidence: 99%
See 1 more Smart Citation
“…However, we would sincerely want that situation to change as soon as possible, so that people with haemophilia in all of Asia-Pacific can receive the same care as those in Luxembourg and Taiwan, whence these authors originate and where cryoprecipitate is not used at all for the treatment of haemophilia. Most critically, at a time when it has been clearly established that prophylaxis is the only way to alter the natural history of severe haemophilia 6 and we are Accepted: 28 April 2018 DOI: 10.1111/hae.13522 strongly advocating for clotting factor concentrates (CFCs) for the same, we do not want to distract attention of the health authorities with wet cryoprecipitate which can hardly be used for prophylaxis.…”
Section: Principles Of Haemophilia Care: the Asia Pacific Perspectivementioning
confidence: 99%
“…Secondly, administration and accessibility of AHF under government initiative predominantly caters to on-demand requirement during an acute bleeding episode, and offering primary prophylaxis in PwH is exceptional. The multicentric, prospective MUSFIH study which included an Indian referral centre concluded that episodic AHF replacement does not alter the natural course of bleeding in hemophilia or the musculoskeletal deterioration [8]. As the country steps towards universal access to AHF, the stakeholders in hemophilia care must envisage a paradigm shift from episodic replacement to primary prophylaxis starting from a young age.…”
Section: E D I T O R I a L E D I T O R I A L E D I T O R I A L E D I mentioning
confidence: 99%